Embedding electronic growth charts into clinical practice at a children's hospital. Issue 2 (9th October 2017) - Andrews, Edward T; Wootton, Stephen; Cable, David; Marchant, Alastair; Miller, Harriet; Davies, Justin H
Abstract : Embedding electronic growth charts (EGCs) into clinical practice in a children's hospital. We employed initial implementation in the outpatient setting and subsequently extended this across inpatients with the growth chart following the child's records through both settings and significantly increasing growth data documentation.